Implementing recommended breastfeeding practices in healthcare facilities in India during the COVID-19 pandemic: a scoping review of health system bottlenecks and potential solutions - Dudeja, Nonita; Sharma, Divita; Maria, Arti; Pawar, Priyanka; Mukherjee, Ritika; Nargotra, Shikha; Mohapatra, Archisman (Frontiers in Nutrition, 2023)
Background: Breastfeeding practices in institutional settings got disrupted during the COVID-19 pandemic. We This scoping reviewed highlights the challenges faced and the 'work-around' solutions identified for implementing recommended optimizing breastfeeding practices in institutionalized mother-newborn dyads in resource constrained settings during the pandemic amidst disruptions caused by the COVID-19 pandemic. Ourwith the aim was to identify learnings that could be potentially adapted to the Indian and relatable contexts, for building resilient health systems. Methods: We conducted a scoping review of literature using The review follows the PRISMA ScR Extension guidelines. The search was conducted inWe searched the Medline via PubMed and Web of Science databases for literature published the period frombetween 1 st December 2019 and 15 th -April 2022. We searched forincluded all study designs including original research, reviews, and policy recommendations published in English language and on for the India while others were excludedn context. Further, we searched for relevant grey literature on Google (free word search), websites of government and major professional bodies in India. Three reviewers independently conducted screening and data extraction and the results were displayed in tabular form. Challenges and potential solutions for breastfeeding were identified and were categorized under one or more suitable headings based on the WHO building blocks for health systems.